Transport of information-carriers in semiconductors & nanodevices - El-Saba, Muhammad, 1960- (Engineering Science Reference, 2017)
"This book contains a comprehensive discussion of the most important topics of information-carrier transport, including some topics not previously presented, altogether, in a single book. The main purpose of this book is to develop an appreciation and a deep understanding for the conceptual foundations underlying the operation of emerging nanoelectronic devices"-- Provided by publisher
Keywords: Electron transport.; Photon transport theory.; Semiconductors -- Transport properties.; elektronické knihy; electronic books